2021
DOI: 10.1111/joca.12413
|View full text |Cite
|
Sign up to set email alerts
|

Identifying consumer segments based on COVID‐19 pandemic perceptions and responses

Abstract: Consumer responses to the COVID-19 pandemic have varied widely. Thus, marketers need to understand consumer segments based on pandemic-related responses and behaviors. Through two studies conducted 9 months apart, we find that consumers shift from three segments in Study 1-the Apprehensive, the Prepared, and the Dismissive, to two segments in Study 2-the Dedicated and the Dismissive. The Apprehensive feel particularly threatened of the virus.The Prepared and the Dedicated perceive a lower susceptibility but st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…Therefore, while modifying media reporting practices may be desirable, it not clear how much of an effect such measures would have vis-à-vis these other factors. It is also apparent from recent research that purchasing patterns in the general population can change over the course of the pandemic, with many "apprehensive" (panic buying) consumers gradually shifting to a "prepared" or "dedicated" behavior pattern characterized by more rational purchasing and safety behaviors (Sheng et al, 2021). If this finding applies in other settings, it is possible that media strategies might have their greatest impact in the initial phase of a pandemic, and that their impact may lessen as individuals develop less anxiety-driven behaviors over time.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, while modifying media reporting practices may be desirable, it not clear how much of an effect such measures would have vis-à-vis these other factors. It is also apparent from recent research that purchasing patterns in the general population can change over the course of the pandemic, with many "apprehensive" (panic buying) consumers gradually shifting to a "prepared" or "dedicated" behavior pattern characterized by more rational purchasing and safety behaviors (Sheng et al, 2021). If this finding applies in other settings, it is possible that media strategies might have their greatest impact in the initial phase of a pandemic, and that their impact may lessen as individuals develop less anxiety-driven behaviors over time.…”
Section: Discussionmentioning
confidence: 99%
“…The closure of many businesses has reduced jobs, it has become more difficult for citizens to find jobs, and unemployment has risen. Such a situation has made the gap between the rich and the poor even greater, and the social classification has become more and more obvious [4].…”
Section: Influence Of Consumersmentioning
confidence: 99%
“…However, none of these studies have shown real effectiveness as society continues to behave without due care or thought and no significant changes have been observed. Given that consumer segments may differ in perceptions, preferences and other characteristics (Meng & Olsen, 2022; Sheng et al, 2021), segmentation may allow decision‐makers to gain insight into the potential effectiveness in their actions and communication strategies across groups of individuals (Stewart, 2022).…”
Section: Introductionmentioning
confidence: 99%